Aux marges de l'emploi: parcours de travailleuses domestiques québécoises, 1950-2000 - Charron, Catherine (Les éditions du remue-ménage, 2018)
Section: 262 pages : illustrations ; 23 cm
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; his4550; histoire; justice sociale; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques; travail; travail domestique

Dancing backwards in high heels: Female professors experience more work demands and special favor requests, particularly from academically entitled students - El-Alayli, Amani; Hansen-Brown, Ashley A.; Ceynar, Michelle (Sex Roles, 2018)
Although the number of U.S. female professors has risen steadily in recent years, female professors are still subject to different student expectations and treatment. Students continue to perceive and expect female professors to be more nurturing than male professors are. We examined whether students may consequently request more special favors from female professors. In a survey of professors (n = 88) across the United States, Study 1 found that female (versus male) professors reported getting more requests for standard work demands, special favors, and friendship behaviors, with the latter two mediating the professor gender effect on professors’ self-reported emotional labor. Study 2 utilized an experimental design using a fictitious female or male professor, with college student participants (n = 121) responding to a scenario in which a special favor request might be made of the professor. The results indicated that academically entitled students (i.e., those who feel deserving of success in college regardless of effort/performance) had stronger expectations that a female (versus male) professor would grant their special favor requests. Those expectations consequently increased students’ likelihood of making the requests and of exhibiting negative emotional and behavioral reactions to having those requests denied. This work highlights the extra burdens felt by female professors. We discuss possible moderators of these effects as well as the importance of developing strategies for preventing them. © 2017, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: amériques; approches et analyses; discipline; femmes professeures; milieux universitaires; projet charge mentale; psychologie; psychologie sociale; rapports sociaux de sexe; régions géographiques; sciences humaines; stéréotypes de genre; thématiques; travail; travail émotionnel; états-unis

The Routledge handbook of gender and violence - Lombard, Nancy (Routledge, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Linking job work hours to women’s physical health: The role of perceived unfairness and household work hours - Thomas, Candice L.; Laguda, Emem; Olufemi-Ayoola, Folasade; Netzley, Stephen; Yu, Jia; Spitzmueller, Christiane (Sex Roles, 2018)
Although the relationship between job work hours and women’s physical health has been examined, limited empirical research examines the family demand conditions that explain this relationship. Given the challenge of integrating work and family demands, we examine the boundary conditions under which job hours relate to women’s physical health by integrating the influences of household work hours, perceived unfairness of division of household labor, and traditional gender ideology. Using a large, multi-national archival dataset, our results show that women working long job hours are more likely to report decreased physical health and that this relationship is moderated by the hours and fairness perceptions of household labor: The lowest physical health was observed at high job hours and high household hours and also when women felt that they did less than their fair share of household labor. However, looking at the slopes of these relationships, the negative relationship between job hours and physical health was stronger when women worked lower household hours or felt that they contributed less than their fair share of household labor—suggesting that maintaining a contribution to household labor might be important for working women. Furthermore, these results suggest that policy and organizational interventions aimed at supporting women’s physical health could take their household labor contributions and fairness perceptions into account when assessing the negative impact of high job work hours. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; conciliation famille-travail; culpabilité; discipline; division sexuelle du travail; famille; projet charge mentale; psychologie; psychologie sociale; périodes historiques; rapports sociaux de sexe; sciences humaines; thématiques; travail; travail domestique

Les cheffes d’entreprise et jeunes entrepreneures de Lomé (Togo) : des « superwomen » de la double journée de travail professionnel et domestique ? - Vampo, Charlotte (Enfances, Familles, Generations, 2018)
Cadre de la recherche : Le Togo, pays à forte tradition commerciale, présente un taux élevé d’activité des femmes. Celles-ci sont encouragées à entreprendre et disposent librement de leurs revenus. Parallèlement, elles ont la charge quasi intégrale du travail domestique. Si la plupart d’entre elles sont cantonnées aux activités informelles, certaines cheffes d’entreprise ont réussi à se faire une place dans la capitale dans des secteurs émergents de l’économie formelle. L’enquête porte sur ces archétypes de l’émancipation féminine par le travail, qui ont fait des études supérieures et qui sont dans des associations qui promeuvent l’entrepreneuriat des femmes et leur empowerment. Objectifs : Cet article explore la manière dont elles adhèrent à la division sexuelle du travail (DST) traditionnelle. Il questionne les ressources dont elles disposent pour gérer leur quotidien entre contraintes familiales et obligations professionnelles dans le but de discuter les reconfigurations dans les rôles genrés. Méthodologie : Pour ce faire, la réflexion s’appuie sur des terrains ethnographiques réalisés à Lomé au cours des cinq dernières années. Une micro-analyse des rapports de genre est privilégiée dans le souci d’appréhender les itinéraires de réussite des entrepreneures dans une approche relationnelle. Le matériel empirique se compose d’entretiens, d’observations en entreprises et en dehors de celles-ci, de discussions informelles et d’un questionnaire sur la répartition des dépenses et des tâches au quotidien. Résultats : Les résultats indiquent que la conciliation travail professionnel-travail domestique est considérée comme un devoir de femme mariée. La principale ressource dont disposent ces femmes pour s’organiser est le transfert des charges domestiques sur d’autres femmes autant au domicile que dans l’entreprise. Conclusions : L’adhésion à la DST est déterminée par la place occupée par le mariage dans la réussite et par des enjeux de reconnaissance sociale associés au rôle reproducteur des femmes. Les cheffes d’entreprise de Lomé ne pourraient pas être les superwomen qu’elles essayent d’être sans le recours à d’autres femmes. Contribution : L’accès des femmes à des postes à fortes responsabilités ne modifie pas complètement les rôles de genre si l’on se penche spécifiquement sur la division sexuelle du travail. La reconfiguration des rapports de genre est partiellement dépendante de l’empowerment économique des femmes. Toutefois, la négociation sociale du statut de cheffe d’entreprise se fait dans la transgression des normes de genre mais surtout dans la perpétuation d’un ordre inégalitaire de genre qui accompagne paradoxalement les changements. Cet article nous invite à reconsidérer l’empowerment comme un processus socio-politique à la fois individuel et collectif.
Keywords: afrique; anthropologie; approches et analyses; conciliation famille-travail; discipline; division sexuelle du travail; droits des femmes*; famille; femmes entrepeneures; histoire et politique; projet charge mentale; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques; togo; travail

Prendre en compte les femmes à bas salaires et racisées - Yerochewski, Carole (Nouveaux Cahiers du socialisme, 2018)
Keywords: amériques; approches et analyses; care; cours; discipline; fem1300; inégalités; mouvement syndical; mouvements des femmes*; premier cycle; québec; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail